Conceptual Design of Quality Management Digitalization for FMCG Industry - Septian Sugestyo Putro; Sugeng Santoso (Syntax Corporation, 2022)
Industry 4.0 era encourage FMCG manufacture industries in Indonesia to continuously innovating through digital technology adoption in their process, including quality management. Quality management digitalization in manufacture industry in Indonesia is now at the level of leaving paperwork documentation and analog communication in quality control; and have started to adopt computerized database and analysis. The absent of national software provider and academic study focusing on quality management digitalization concept has become an obstacle for Indonesia to evolve in Industry 4.0 era. This paper intended to provide conceptual design of integrated quality management digitalization to support FMCG industries in effective decision making and compliance to quality control plan; and to stimulate national software provide to develop digitalized quality management program